THE EVOLUTION OF WEBSITE DESIGN AS A RESULT OF ADAPTING MARKETING TOOLS TO CHANGES IN THE PSYCHOLOGICAL PERCEPTION OF INFORMATION BY TARGET AUDIENCES - MYKHAILOV Аrtem; YOKHNA, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes the evolution of website design as an adaptive process, focusing on how marketing tools have evolved in response to shifts in target audiences’ psychological perception of information. It examines contemporary web design trends, including adaptability, minimalism, personalization, and inclusivity, which are increasingly utilized by commercial enterprises to enhance user convenience and conversion rates. The study identifies a heightened focus on optimizing cognitive load, as users’ cognitive capacities are often challenged by the demands of modern digital interfaces. Consequently, understanding and reducing cognitive load has become a priority in web design, ensuring that users can access content effectively without experiencing frustration. The research further explores how emotional design—through strategic use of visuals, colors, and interactive elements—plays a critical role in engaging and retaining user attention. By aligning design elements with psychological preferences, emotional design enhances the overall user experience, contributing to greater user satisfaction and loyalty. This approach is particularly effective in sectors like e-commerce, where emotional resonance can significantly impact user decisions and conversions. Additionally, the article discusses the relevance of psychotemporal marketing for maintaining long-term user engagement. Despite the broad adoption of modern design approaches across various sectors, including education and public services, there remains a gap in the optimal use of psychotemporal strategies to sustain prolonged interaction. Addressing this need is crucial as the digital landscape continually adapts to evolving user behaviors and expectations. The findings of this study offer actionable insights for marketing and design professionals, providing guidelines for aligning web design with current psychological insights into user behavior. By fostering an environment that is intuitively navigable, emotionally appealing, and tailored to user needs, brands can enhance their online presence and improve conversion outcomes. Furthermore, the study underlines the need for continued exploration of psychological principles in web design, encouraging future research on the intersections between user psychology and digital marketing strategies.